Study of CP violation in the process of associated Higgs boson production with a decay into muon pair. (November 2019) - Belyaev, N; Konoplich, R; Prokofiev, K; Reese, T
Abstract: After the Higgs boson discovery at the LHC, a lot of additional measurements should be performed to understand in detail the properties of the observed particle. Searches for CP violation in different physics sectors are one of the most promising and important parts of these measurements. Associated Higgs boson production in pp collisions can be a powerful tool for searches for possible CP violation in the Higgs sector. In this paper, the study of CP sensitive observables constructed for a four lepton final state is presented. It is shown that azimuthal angle distributions of leptons in this process demonstrate a strong sensitivity to CP violation at the current limits on Higgs boson coupling parameters and can reveal a genuine mechanism of CP violation.